2003
DOI: 10.1246/cl.2003.1110
|View full text |Cite
|
Sign up to set email alerts
|

Organic–Inorganic Cooperative Molecular Recognition in Nanostructure of Alkyl-grafted MCM-41

Abstract: Molecules having hydrophobic and hydrophilic groups such as 4-n-heptylaniline and 4-nonylphenol, an endocrine disrupter, fit the organic–inorganic nanostructure in alkyl-grafted MCM-41, interacting with the inorganic walls as well as the organic moiety, and thus the adsorbent achieves high molecular adsorption selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 17 publications
2
10
0
1
Order By: Relevance
“…Entscheidend für die Optimierung der Eigenschaften ist dabei die Feinabstimmung der Polarität der inneren Struktur. Inumaru et al erzielten interessante Ergebnisse hinsichtlich des Adsorptionsverhaltens von Alkylphenolen und Alkylanilinen in MCM‐41‐Festkörpern 107. Sie präparierten eine Reihe verschiedener Festkörper, modifizierten deren Oberfläche mit Alkylketten unterschiedlicher Länge und dotierten das Wirtmaterial zusätzlich mit unterschiedlichen Konzentrationen an Al 3+ .…”
Section: Biomimetische Und Gesteuerte Supramolekulare Chemie Von Hunclassified
“…Entscheidend für die Optimierung der Eigenschaften ist dabei die Feinabstimmung der Polarität der inneren Struktur. Inumaru et al erzielten interessante Ergebnisse hinsichtlich des Adsorptionsverhaltens von Alkylphenolen und Alkylanilinen in MCM‐41‐Festkörpern 107. Sie präparierten eine Reihe verschiedener Festkörper, modifizierten deren Oberfläche mit Alkylketten unterschiedlicher Länge und dotierten das Wirtmaterial zusätzlich mit unterschiedlichen Konzentrationen an Al 3+ .…”
Section: Biomimetische Und Gesteuerte Supramolekulare Chemie Von Hunclassified
“…[4] The grafting of organic groups onto the pore walls of the silica [5] has provided novel materials for catalysis, [6] heavy-metal ion adsorption, [7] photocontrollable molecular storage, [8] gas separation, [9] and molecular recognition. [10][11][12] Since the chemical functionalities of these materials have been ascribed mainly to the organic moiety, a promising strategy toward new functions is to design an inorganic-organic cooperative mechanism in nanostructured materials. [11,12] Solid acid catalysts have served as important functional materials in about 180 industrial processes in the petroleum refinery industry and in the production of chemicals.…”
mentioning
confidence: 99%
“…[10][11][12] Since the chemical functionalities of these materials have been ascribed mainly to the organic moiety, a promising strategy toward new functions is to design an inorganic-organic cooperative mechanism in nanostructured materials. [11,12] Solid acid catalysts have served as important functional materials in about 180 industrial processes in the petroleum refinery industry and in the production of chemicals. [13] In contrast, a significant number of acid-catalyzed reactions, such as Friedel-Crafts reactions, esterification, and hydrations, are still carried out by using conventional acids, such as H 2 SO 4 and AlCl 3 .…”
mentioning
confidence: 99%
“…The fine‐tuning of the inner polarity of such structures is a key step toward improved responses. In this respect, Inumaru et al reported interesting results on the adsorption behavior of alkyl phenols and alkyl anilines by MCM‐41 solids 107. They prepared a series of solids and grafted not only alkyl chains of different length onto the surface, but also doped the host material with different concentrations of Al 3+ ions.…”
Section: Biomimetic and Gated Supramolecular Chemistry In Hybrid Nmentioning
confidence: 99%